2022
DOI: 10.51414/sei2022.040
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and the World of Work: Policies, Initiatives and the Current Situation – A Scoping and Evidence Review for Southeast and East Asia.

Abstract: This scoping report synthesizes the authors’ initial work to understand the differentiated impacts of air pollution on workers in East and Southeast Asian countries and to identify evidence-based recommendations from regional case studies to help improve air quality and foster healthy employment in the context of just transitions towards a low-carbon economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…For example, men are more likely to work in traffic-facing roles such as drivers or traffic police, which involve high pollution exposure, on top of pre-existing exposure to ambient and domestic air pollution. Men in Southeast Asia suffer more years of life lost due to occupational exposures to particulate matter, gases and fumes (Slater et al, 2022). These findings indicate that men, depending on occupational type, are equally, if not more, susceptible to air pollution impacts than women facing domestic exposure -yet this perspective is not well captured in existing literature on gender and air pollution.…”
Section: Source: Authors' Ownmentioning
confidence: 91%
See 3 more Smart Citations
“…For example, men are more likely to work in traffic-facing roles such as drivers or traffic police, which involve high pollution exposure, on top of pre-existing exposure to ambient and domestic air pollution. Men in Southeast Asia suffer more years of life lost due to occupational exposures to particulate matter, gases and fumes (Slater et al, 2022). These findings indicate that men, depending on occupational type, are equally, if not more, susceptible to air pollution impacts than women facing domestic exposure -yet this perspective is not well captured in existing literature on gender and air pollution.…”
Section: Source: Authors' Ownmentioning
confidence: 91%
“…A scoping review by Slater et al (2022) of research papers on air pollution in the world of work in southeast Asia carried out three specific searches of existing literature in the region. The first, a literature search on gender and intersectionality related to air pollution and work, found that research on the impacts of air pollution is framed largely by a medical health and public health perspective, rather than on the lived experiences of exposed groups.…”
Section: Source: Authors' Ownmentioning
confidence: 99%
See 2 more Smart Citations
“…Vehicle emission standards should also be applied (such as Euro 4 or above) while fuel sulphur content limits should be introduced that are in line with other South-East Asian countries. (These are currently at 2000 ppm, whereas most countries in South-East Asia limited to 10-50 ppm) (Slater et al 2022). Myanmar could consider leapfrogging.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%